Simultaneous Effects of Hydrostatic Pressure and External Electric Field on the Energy Spectra of Two Donors in a Strained Zinc Blende GaN/AlGaN Quantum Dot (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
The energy spectrum of two donors in a strained GaN quantum dot embedded in Al\(_x\)Ga\(_{1-x}\)N has been investigated under the influence of hydrostatic pressure and external electric field. Our calculations are carried out using variational principle within the single band effective mass approximation by means of dot radius, hydrostatic pressure, and electric field. The numerical results show that the binding energy of two donors increase, attains a maximum value, and then decreases as the quantum dot radius increases for any electric field. Moreover, the binding energy of two donors increases with the pressure for any size of dot. Our results are compared with existing literature.
Keywords: Strained quantum dot; Variational method; Hydrostatic pressure; Electric field